A pressure process for efficient and stable perovskite solar cells. (November 2020) - Luo, Junsheng; Xia, Jianxing; Yang, Hua; Sun, Chunlin; Li, Ning; Malik, Haseeb Ashraf; Shu, Hongyu; Wan, Zhongquan; Zhang, Haoli; Brabec, Christoph J.; Jia, Chunyang
Abstract: The grain boundaries of organic-inorganic halide perovskite films not only function as defect centers, but also behave as intrinsic ion migrating channels and extrinsic moisture-induced degradation initiators, which are detrimental to the efficiency and stability of perovskite solar cells (PSCs). Here, an effective methodology for fabrication of high-quality perovskite layers with reduced non-radiative recombination, suppressed ion migration and increased moisture stability is reported for the first time, referred as the pressure-assisted solution processing (PASP). Through PASP strategy, the nucleation and growth of perovskite crystals can be controlled, leading to the micron-sized grains and microsecond-range carrier lifetimes. The resultant PSC shows champion power conversion efficiency (PCE) as high as 20.74% and a stabilized efficiency exceeding 20%, with superior long-term stability, maintaining above 90% of initial PCE even aging 60 days and continuous 1-sun illumination for 200 h in ambient environment without encapsulation. We unambiguously believe that the control of perovskite crystal nucleation and growth with high quality will be an important direction to improve the efficiency of PSCs to the theoretical limit, as well as to stabilize perovskite-based materials and devices. Graphical abstract: Pressure-assisted solution processing (PASP) is demonstrated for fabrication of highly crystallized perovskite films with micron-sized grains, microsecond-range carrier lifetimes and low non-radiative recombination, the resultant PSC shows a stabilized efficiency exceeding 20%. Image 1 Highlights: Micron-sized grains of perovskite crystals have been obtained by PASP strategy. PASP-perovskite films show low defects density and microsecond-range carrier lifetime. The champion PCE of 20.74% (stabilized at 20.33%) has been achieved for PASP-PSC. PASP-perovskite can suppress intrinsic ion migration and extrinsic moisture degradation.